2020
DOI: 10.1177/0825859720933112
|View full text |Cite
|
Sign up to set email alerts
|

Translating Pediatric Hospital Interpreters’ Feedback From Difficult Conversations into Improved Communication

Abstract: Background: Medical interpreters are critical mediators in communication with pediatric subjects and families to include participation in difficult conversations. Objective: The objective of this pilot study was to provide suggestions from medical interpreters to palliative care teams as to how to effectively incorporate medical interpreters into end-of-life conversations. Subjects and Method: Participants included pediatric hospital-based medical interpreters who had interpreted for at least 1 end-of-life con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The 10 studies included in this review are all studies published in peer-reviewed journals. They utilized 1 or more of the following data collection techniques: semi-structured interviews (n = 5) (Hordyk et al 2017;Kirby et al 2017;Latif et al 2022a;Rhodes et al 2021;Silva et al 2020), surveys (n = 4) (James and Crawford 2021; Schenker et al 2012;Silva et al 2022;Weaver et al 2022) and observation (n = 1) (Hordyk et al 2017). Most of the studies included examined the perspectives of the medical interpreters themselves (Hordyk et al 2017;James and Crawford 2021;Kirby et al 2017;Latif et al 2022a;Norris et al 2005;Rhodes et al 2021;Schenker et al 2012;Silva et al 2020;Weaver et al 2022), while 1 study analyzed the perspectives of both training and attending level physicians (Silva et al 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 studies included in this review are all studies published in peer-reviewed journals. They utilized 1 or more of the following data collection techniques: semi-structured interviews (n = 5) (Hordyk et al 2017;Kirby et al 2017;Latif et al 2022a;Rhodes et al 2021;Silva et al 2020), surveys (n = 4) (James and Crawford 2021; Schenker et al 2012;Silva et al 2022;Weaver et al 2022) and observation (n = 1) (Hordyk et al 2017). Most of the studies included examined the perspectives of the medical interpreters themselves (Hordyk et al 2017;James and Crawford 2021;Kirby et al 2017;Latif et al 2022a;Norris et al 2005;Rhodes et al 2021;Schenker et al 2012;Silva et al 2020;Weaver et al 2022), while 1 study analyzed the perspectives of both training and attending level physicians (Silva et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…They utilized 1 or more of the following data collection techniques: semi-structured interviews (n = 5) (Hordyk et al 2017;Kirby et al 2017;Latif et al 2022a;Rhodes et al 2021;Silva et al 2020), surveys (n = 4) (James and Crawford 2021; Schenker et al 2012;Silva et al 2022;Weaver et al 2022) and observation (n = 1) (Hordyk et al 2017). Most of the studies included examined the perspectives of the medical interpreters themselves (Hordyk et al 2017;James and Crawford 2021;Kirby et al 2017;Latif et al 2022a;Norris et al 2005;Rhodes et al 2021;Schenker et al 2012;Silva et al 2020;Weaver et al 2022), while 1 study analyzed the perspectives of both training and attending level physicians (Silva et al 2022). In the 9 studies that focused on medical interpreters' perspectives, the interpreters worked with patients who spoke a wide range of languages, with the most common being Spanish (Hordyk et al 2017;James and Crawford 2021;Kirby et al 2017;Latif et al 2022a;Norris et al 2005;Rhodes et al 2021;Schenker et al 2012;Silva et al 2020;Weaver et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…17 Professional medical interpreters are required to interpret everything being said by both parties in the health care visit. Medical interpreters shared 7 thematic suggestions for improved communication in language-discordant visits 18 (Table 2). 17 As experts in cultural dynamics and message transmission, PMIs have insights that can improve communication with families of patients.…”
Section: Professional Medical Interpretersmentioning
confidence: 99%
“…Although secondary traumatic stress (STS) and vicarious trauma have been investigated in medical interpreters caring for refugees and other populations, there is minimal quantitative data regarding the emotional impact of palliative care encounters on medical interpreters (Goldhirsch et al, 2022). Research has demonstrated medical interpreters play many roles when interpreting for palliative care patients such as interpreting language and meaning, acting as a cultural broker, and advocating for patients and families (Hordyk et al, 2017;Kirby et al, 2017;Latif et al, 2022a;Silva et al, 2020;Slusarz, 2023;Weaver et al, 2022). Interpreters have reported that navigating these complex and sometimes contradicting roles can present moral and ethical dilemmas that can cause emotional distress (Hordyk et al, 2017;Kirby et al, 2017;Norris et al, 2005;Rhodes et al, 2021;Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In qualitative studies, interpreters have reported that participating in palliative care encounters requires compartmentalization or suppression of their emotions (Kirby et al, 2017; Schenker et al, 2010; Silva et al, 2020). The emotional burden of the encounters has been reported to be linked to the content of the conversation and the emotional intensity of the participants (Weaver et al, 2022).…”
Section: Introductionmentioning
confidence: 99%